Experimental evaluation of a R-EAM and noise impact analysis for UWB and Wi-Fi transmission in RoF networks - L. M. Pessoa (2013)
The performance of a reflective electro-absorption modulator transceiver is assessed in terms of both slope efficiency (SE) and responsivity in a radio-over-fiber network. Different biasing schemes are analyzed, specifically zero bias (passive solution), bias for maximum SE, and bias for maximum responsivity. Finally, two case studies on multiband orthogonal frequency division multiplexing ultra-wide band and Wi-Fi are presented, for which the optimum setup parameters are determined.